Pengaruh Pelatihan dan Motivasi Terhadap Kinerja Operator Produksi PT. Alam Lestari Unggul - Lukman Nul’ Hakim (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
Nowadays, competitiveness increase continuously and influenced by quality of its people. Performance improvement of human resource in a company can be reached by several ways. There are several factors that influence peoples in a company, such as training and motivation. This research is to examines the impact of training and motivation toward operation employees performance. Population of this research are 400 respondances and 80 samples. This research is conducted in one of welding electrode manufacturer company called PT Alam Lestari Unggul. The result of the reasearch shows that both training and motivation positifly and significantly influences operators’ performance in PT Alam Lestari Unggul both partially and simultanousley. The conclution of this research is production operators performance can be increased using two ways, enhancing training effectiveness and designing work environment to develop employee motivation.